Disparities of obesity and non-communicable disease burden between the Tibetan Plateau and developed megacities in China - Peng, Wen; Jian, Wenxiu; Li, Tiemei; Malowany, Maureen; Tang, Xiao; Huang, Mingyu; Wang, Youfa; Ren, Yanming (Frontiers in Public Health, 2023)
Abstract Background: Non-communicable diseases (NCDs) including risk factors, e.g., obesity, are the major causes of preventable deaths in China, yet NCD disparities in China remain under- studied. Objective: To compare the determinants and burden of NCDs within four selected provinces in mainland China: the least developed Qinghai-Tibet Plateau group (PG,Tibetan Autonomous Region [TAR] and Qinghai Province) and most developed mega-city group (MCG,Shanghai and Beijing). Methods: Studies, reports and other official sources with comparable data for NCD burden and related determinants for the four provinces were searched. Geographic, demographic, socioeconomic, and dietary characteristics and selected health indicators (e.g., life expectancy) were extracted from the China Statistical Yearbook and China Health Statistics Yearbook. Data on NCD burdens were extracted from the National Chronic Disease and Risk Factor Surveillance Study and other nationally representative studies. Results: The overall NCD mortality rates and prevalence of metabolic risk factors including obesity, hypertension and diabetes in mainland China have increased in the past 20 years and this trend is expected to continue. The Plateau group (PG) had the highest level of standardized mortality rates (SMRs) on NCDs (711.6-896.1/100,000, 6th /6-level); the mega-city group (MCG) had the lowest (290.6-389.6/100,000, 1st/6-level) in mainland China. The gaps in SMRs were particularly high with regard to chronic respiratory diseases (PG 6th/6-level, MCG 1st/6-level) and cardiovascular diseases (6th/6 and 4th/6 in TAR and Qinghai; 1st/6-level and 2nd/6-level in Shanghai and Beijing). By contrast, the prevalence rates of obesity, hypertension and diabetes were generally higher or comparable in MCG compared to PG. Diabetes prevalence was particularly high in MCG (5th/5-level, 13.36%-14.35%) and low in PG (1st/5-level, 6.20%-10.39%). However, awareness, treatment and control of hypertension were poor in PG. Additionally, PG had much lower and severely inadequate intakes of vegetables, fruits, dairy products, with additional indicators of lower socioeconomic status (education, income, etc.) compared with MCG. Conclusions: Evidence showed large disparities in NCD burden in China ’s provinces. Socioeconomic disparity and dietary determinants are probably reasons. Integrated policies and actions are needed.